HUBUNGAN ANTARA IKLIM ORGANISASI DENGAN INTENSI TURNOVER PADA PEGAWAI PDAM TIRTA MOEDAL KOTA SEMARANG - Yoga Aji Nugraha; Anita Listiara (Faculty of Psychology, Diponegoro University, 2017)
This study aims to determine the relationship between organizational climate with turnover intention on the employee PDAM Tirta Moedal Semarang City. Turnover intention is the individual’s desire to leave the company or organization. Organizational climate is the individual’s perception of his work environment, viewed, observed and perceived by individuals as members of the organization and then given meaning by individuals based on their interperetation of the environmental situation. The subject of research is 78 employees of PDAM Tirta Moedal Semarang City obtained with cluster random sampling technique. The measuaring instruments used in this research are turnover intention scale (25 items, α = .884) and organizational climate scale (45 aitem, α = .954). data analysis method used in this research is simple regression analysis. The results showed that there ws a significant negative relationship between organizational climate with turnover intention (r = -.758; p = .000; p <0.05). Organizational climate contributes 57.5% to turnover intentions.